PERANCANGAN VIDEO PROMOSI 3D JANJANG TOUR AND TRAVEL PARIWISATA MINANGKABAU SUMATERA BARAT - Pradana, Getar; Hasni, Fatimah Yasmin (Anggada : Jurnal Desain dan Seni, 2021)
There are various kinds of promotional media that are developing today, from promotional media by means of oral, written and visual communication. The oldest promotion is word of mouth. This promotion was found in ancient times so that in today’s technological developments we have encountered many promotional media in the form of brochures, pamphlets, fliers, posters, billboards, advertisements in newspapers and so on. Minangkabau, which is located in West Sumatra, has high tourism potential because it is a beautiful tourism city. However, from 2018 until now there has been a decline in tourism visiting the area. Due to promotions that are still offline, not online, so the reach is limited and the current decline is due to the pandemic which makes it difficult to get promotional video or photo assets. So the authors provide solutions in promotion to be able to increase more consumers.